How much meat from a steer? - Mackintosh, D.L.; Henrickson, R.W.; Watt, D.B. (Kansas Agricultural Experiment Station, 2012)
How much meat should I have in my locker from a 1000 pound steer? This is the type of question that is asked most frequently by locker patrons. Many people, now using frozen food lockers have little conception of how much meat, the number of pieces, or the type of cuts that they should expect from one carcass. Neither do they realize what happens to a large part of a steer before reaching the locker. Actually a 1000 pound steer will yield approximately 180 pounds of steaks of varied kinds, 180 pounds of roast and pot roasts, and 90 pounds of stew and ground meat making a total of 450 pounds of table meat which is 45 percent of the live weight of the animal. A comparable shrinkage occurs when a hog or a lamb is butchered.
Keywords: Meat; Meat locker; Carcass